Scale Up Business dan Digitalisasi Tata Kelola BUMDes Retno Sembodo dalam Membentuk Kemandirian Ekonomi Masyarakat - Wardana Wardana; Hafizh Fitrianna; Suhartanto Suhartanto (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this community service activity is to improve organizational governance capabilities for BUMDes Retno Sembodo managers and provide digital literacy counseling, financial literacy and entrepreneurial insight for residents of Baturetno Village, Banguntapan District, Bantul Regency, Yogyakarta. The method used is offline counseling and mentoring. The implementation of activities is divided into 3 stages, namely pre-implementation including observation and identification of problems; the implementation phase includes organizational governance training, digital and financial literacy counseling; and the post-implementation stage includes mentoring and increasing business scale. The product output from this service activity is the BUMDes Retno Sembodo website which is used as a medium of information as well as a branding profile. The result of the implementation of this service is an increase in the ability and insight of BUMDes manager Retno Sembodo and Baturetno village residents regarding organizational management governance, digital literacy, financial literacy and entrepreneurial insight. The implication of the results of this service is the development of a BUMDes management guide model that can be used as a reference in the digital transformation process and increase the business scale of its business units.